Challenges faced by middle management at Shoprite Holdings LTD - Malemela, Lesabe Thomas (University of Limpopo, 2017)
Middle management at Shoprite faced challenges and their role is diverse and they lack strategies to cope with challenges within the organisation.Middle managers, in trying to balance the needs of senior and junior managers, often feel like ‘piggy-inthe- middle’, with potential for conflict and tension (McConville, 2006; Floyd and Wooldridge, 1992). A lack of leadership from senior management may compromise middle managers’ ability to take a professional approach to managing their area. Middle managers in Shoprite say that they want to be more professional Burgess, (2011)but are being inhibited by the lack of support and awareness from senior managers, with a negative impact on their motivation and their job satisfaction. In addition lack of middle manager’s involvement in decision making and strategy formulation. Middle managers become reluctant to change due to lack of communication on strategy alteration. This study intends to investigate the challenges faced by middle management at Shoprite Holdings Limited in Limpopo Province. The findings of the study show that the roles are challenging and varied, strategy implementation is a major challenge and support for middle managers is generally insufficient. Middle managers require support in induction into the middle management role and ongoing mentoring and appraisal. The little studies have been conducted about the challenges faced by middle management from different perspectives and organisations. Finally, further research into the challenges faced by middle management at Shoprite Holdings Ltd is required as it could either endorse or challenge the findings of this study and might also inform Top management about the Challenges faced by middle management and prompt an evaluation of the existing role, challenges and needs. Key words; Middle management
Thesis (MBA) --University of Limpopo, 2017
Keywords: Middle Management; Shoprite; Middle managers; Chain stores